Clinical and histopatological investigations on repairing large defected hernias by synthetic tulle - Yılmaz Koç; M. Kemal Çiftçi; Celal İzci; S. Serap Türkütanıt; Mustafa Arıcan (Eurasian Journal of Veterinary Sciences)
ln this study in order to close the large defected umbilical and abdominal hernias synthetic tulle that is economic, close tressed easily extend, lasting and abudantfy found was used.